2005
DOI: 10.1007/s10450-005-6028-y
|View full text |Cite
|
Sign up to set email alerts
|

On the Reversibility of Hydrogen Storage in Novel Complex Hydrides

Abstract: Abstract.A comparison of the hydrogen release and uptake (cycling) capability of Ti-doped NaAlH 4 , LiAlH 4 and Mg(AlH 4 ) 2 as a function of Ti dopant concentration, temperature, pressure, and cycle number is reported. Temperature programmed desorption revealed hydrogen release capacities of around 3 wt% at 140 o C, 3 wt % at 100 o C and 6 wt% at 150 o C, respectively for the Ti doped Na, Li and Mg alanates. In the same order, release capacities of 0.5, 2.0 and 1.5 wt% were obtained in 150, 6 and 150 min duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 13 publications
1
39
0
Order By: Relevance
“…When doped with a Ti catalyst [1][2][3][4][5], this material discharges reasonable amounts of hydrogen at atmospheric pressure at about 80 • C lower than un-doped NaAlH 4 [6]. More importantly, the Ti catalyst also facilitates a kinetic pathway for reversibility, with reasonable charge rates achieved at around 125 • C and 1200 psia [3,[7][8][9][10]. Although this material has a theoretical potential to reversibly store 5.6 wt% hydrogen, numerous studies have shown that the state-of-the-art is around 3 wt% reversible hydrogen storage at reasonable temperatures, pressures, and discharge and charge rates [3,[6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 92%
“…When doped with a Ti catalyst [1][2][3][4][5], this material discharges reasonable amounts of hydrogen at atmospheric pressure at about 80 • C lower than un-doped NaAlH 4 [6]. More importantly, the Ti catalyst also facilitates a kinetic pathway for reversibility, with reasonable charge rates achieved at around 125 • C and 1200 psia [3,[7][8][9][10]. Although this material has a theoretical potential to reversibly store 5.6 wt% hydrogen, numerous studies have shown that the state-of-the-art is around 3 wt% reversible hydrogen storage at reasonable temperatures, pressures, and discharge and charge rates [3,[6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 92%
“…Ti-doped NaAlH 4 , and to a lesser extent, other metal-doped complex hydrides [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63], are being studied with earnest to determine their potential as a new class of reversible hydrogen storage materials. To date, however, only the metal-catalyzed NaAlH 4 system has been shown to be reversible, with Ti-doped NaAlH 4 providing around 3 wt.% hydrogen at around 100 • C [16,32].…”
Section: Introductionmentioning
confidence: 99%
“…The direct rehydrogenation of LiH þ Al has not been conclusively demonstrated in the literature. No hydrogen absorption was observed in pressure range of 7e10 MPa [6,10,22,23] while partial rehydrogenation of Eq. (2) was reported under similar conditions or even lower pressures [11,24e26].…”
Section: Introductionmentioning
confidence: 99%